Modernisasi Sekuler dan Krisis Identitas sebagai Akar Revolusi Iran 1979 - Fatimah Hs; Muhammad Yunus; Muhammad Jusman Rivay Rumra; Hasaruddin; Rahmawati (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
The 1979 Iranian Revolution stands as a pivotal event in modern Islamic history, driven not only by political and economic factors but also by an identity crisis resulting from the Pahlavi Dynasty's secular modernization project. This study aims to analyze the relationship between secular modernization, the identity crisis within Iranian society, and the emergence of the revolution as a response to the state's cultural delegitimization. Utilizing a literature review method with a historical-analytical approach, data were gathered from relevant primary and secondary sources and analyzed qualitatively through historical interpretation to trace the causal links between modernization, the marginalization of religious institutions, and revolutionary mobilization. The findings indicate that the top-down, Western-oriented secular modernization initiated by the regime created social dislocation and a profound identity crisis. The secularization of public institutions, the marginalization of the ulama (clergy), and the penetration of Western culture weakened the cultural legitimacy of the Pahlavi regime. In this context, Islam was rearticulated by scholars and intellectuals as an ideology of resistance, capable of mobilizing diverse social groups into a revolutionary movement. In conclusion, the 1979 Iranian Revolution was not merely a consequence of political and economic failure, but also the result of a conflict between the state's secular modernization project and the religio-cultural identity of the people. These findings emphasize that modernization processes insensitive to a society's identity structures have the potential to trigger state delegitimization and the resurgence of political Islam.